Malignant behaviors and immune response in melanoma: Epstein-Barr virus induced gene 3 as a therapeutic target based on an in-vitro exploration - Zhang, Ying; Cheng, Fengrui; Cai, Xingrui; Wu, Jingping (PeerJ, 2024)
Background Epstein-Barr virus induced gene 3 (EBI3), a member of the IL-12 family, is known to be involved in malignant progression in a variety of cancers, but its role in melanoma is unclear. The aim of this study was to explore the effects of EBI3 on the malignant phenotype melanoma to reveal its potential as a therapeutic target. Methods In this study, we used bioinformatics to analyze the expression of EBI3 in pan-cancer and verified its expression level in melanoma cells by reverse transcription-quantitative polymerase chain reaction (RT-qPCR). Subsequently, the effects of EBI3 knockdown on cell proliferation, migration and invasion were detected using the Cell Counting Kit-8 (CCK-8) and Transwell assays. Changes in immune-related cytokines were detected by ELISA, and macrophage polarization was observed using immunofluorescence. Finally, the phosphorylation levels of signaling pathways such as Smad3, STAT6 and cGAS-STING were analyzed by Western blot. Results EBI3 was evidently highly-expressed in melanoma, and silencing of EBI3 could visibly suppress the survival and migration/invasion of melanoma cells, concurrent with the increased levels of BAX and CDH1 and the decreased expressions of BCL2 and CDH2. Meanwhile, EBI3 knockdown diminished the phosphorylation levels of both Smad3 and STAT6 and the levels of immune response-relevant cytokines in melanoma cells, while aggravating the macrophage M1 polarization and the expression of cGAS, p-STING and p-IRE1 α in THP-1 monocyte-derived macrophages co-cultured with EBI3-silenced melanoma cells. Conclusion This study filled the blank on the involvement of EBI3 in melanoma, hinting the possibility of controlling EBI3 as a therapeutic strategy in the management of melanoma.
Keywords: Malignant behaviors; Immune response; Melanoma; Macrophage; Epstein-Barr Virus Induced Gene 3